Evaluation of the Performance of the Regional Medium Term Development Plan (RPJMD) for the 2023 Period by Bappeda Ciamis: Review of the Achievements of Main Performance Indicators (IKU) - Ela Nurlaela; Mel Asni; Adelia Riani Putri; Regi Refian Garis; Tommy Bektania; Kiki Endah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The Regional Medium-Term Development Plan (RPJMD) is an important instrument in regional development planning that aims to direct development policies for five years. The 2019-2024 RPJMD of Ciamis Regency is a strategic foundation for the Regional Government. This document not only regulates development priorities but also sets performance indicators to measure the achievement of development goals. This research uses a descriptive qualitative approach to evaluate the implementation of the RPJMD by the Regional Development Planning Agency (Bappeda) of Ciamis Regency. Data was collected through semi-structured interviews with Bappeda officials and staff directly involved in the implementation of the RPJMD. The evaluation results show very significant achievements in Key Performance Indicators (KPI) such as the increase in the Percentage of Independent Village Improvement by the Village Community Empowerment Office (DPMD).